Getting control of your anger : - Allan, Robert (McGraw-Hill, 2006)
Getting Control of Your Anger helps adults who have "inherited" destructive anger patterns learn constructive ways to express themselves and get their needs met. Focusing on breaking the cycle of anger, Dr. Allan helps you discover the reasons for your anger, find more constructive ways to get your core needs met, and break the cycle by avoiding passing destructive patterns along to your children.